Enhancing Junior High School Students' Reading Comprehension: The Effectiveness of Directed Reading Thinking Activity Technique - Azzahra, Gia Arya (International Journal of English Language and Pedagogy, 2024)
This study explores the efficacy of the Directed Reading Thinking Activity (DRTA) technique in enhancing reading comprehension among Junior High School students. Addressing a gap in traditional reading strategies, the research aimed to assess whether DRTA could improve comprehension of narrative texts for eighth graders at MTSN 2 Bandar Lampung. Employing a mixed-methods approach, the study utilized pre-tests, post-tests, and student questionnaires to gather both quantitative and qualitative data. The experimental group, which received DRTA instruction, showed significant improvements in post-test scores compared to their pre-test results, indicating enhanced comprehension skills. Qualitative feedback further revealed increased student engagement and motivation. The findings confirm that DRTA not only aids in comprehension but also promotes critical thinking and a deeper understanding of texts. Consequently, the study recommends the integration of DRTA into reading curriculums to meet contemporary educational demands and improve student learning outcomes effectively. This technique promises to bridge the gap between current educational practices and the evolving needs of students in the digital era